148 Identification of prostate-restricted epithelial antigens for transgenic T cell adoptive therapy against prostate cancer. (9th November 2020) - DeLucia, Diana; Pariva, Tiffany; Strong, Roland; Witte, Owen; Lee, John
Abstract : Background: In advanced prostate cancer (PCa), progression to castration-resistant PCa (CRPC) is inevitable and novel therapies for CRPC are needed. Adoptive transfer of T cells targeting tumor antigens is a promising approach in the cancer field. Unfortunately, identifying antigens expressed exclusively in prostate tumor cells has been challenging. Since the prostate is not an essential organ, we alternatively selected prostate-restricted epithelial antigens (PREAs) expressed in both malignant and normal prostate tissue for transgenic T cell studies. Methods: RNA-seq data sets identifying genes enriched in PCa were cross-referenced with the NIH Genotype-Expression database to identify PREAs. Using a novel molecular immunology approach, select PREAs and major histocompatibility complex class I (MHC-I) molecules were co-expressed in HEK293F cells, from which MHC–peptide complexes were efficiently isolated. Peptides were eluted and sequenced by mass spectrometry. Peptide–MHC binding was validated with a T2 stabilization assay and peptide immunodominance was determined using an interferon-γ (IFN-γ) ELISpot assay following stimulation of healthy HLA-A2+ peripheral blood mononuclear cells (PBMC) with peptide pools. Following peptide stimulation, CD8+ T cells with peptide-specific T cell receptors (TCR) were enriched by peptide–MHC-I dextramer labeling and fluorescence activated cell sorting for single cell TCR α/β chain sequencing. Results: We identified 11 A2+ peptides (8 previously unpublished) from prostatic acid phosphatase (ACPP), solute carrier family 45 member 3 (SLC45A3), and NK3 homeobox 1 (NKX3.1) that bound to HLA-A2 with varying affinities. Extended culture stimulation of PBMC with peptide pools from each PREA, compared to the standard overnight culture, revealed a greater number of IFN-γ producing cells overall and a greater breadth of response across all the peptides. Antigen specific CD8+ T cells were detectable at low frequencies in both male and female healthy PBMC for 7 of the 11 peptides. Dextramer-sorted antigen-specific cells were used for single-cell paired TCR αβ sequencing and transgenic T cell development. Conclusions: Through this work we identified HLA-A2-presented antigenic peptides from the PREAs ACPP, SLC45A3, and NKX3.1 that can induce the expansion of IFN-γ producing CD8+ T cells. Through peptide–MHC-I dextramer labeling, we isolated PREA-specific CD8+ T cells and characterized TCR αβ sequences with potential anti-tumor functionality. Our results highlight a rapid and directed platform for the development of MHC-I-restricted transgenic CD8+ T cells targeting lineage-specific proteins expressed in prostate epithelia for adoptive therapy of advanced PCa.